2018
DOI: 10.1523/eneuro.0418-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 1 Type I Overexpression Is Associated with Reduced NMDA Receptor–Mediated Synaptic Signaling in Hippocampal Interneurons Expressing PV or CCK

Abstract: Hypofunction of N-methyl-d-aspartate receptors (NMDARs) in inhibitory GABAergic interneurons is implicated in the pathophysiology of schizophrenia (SZ), a heritable disorder with many susceptibility genes. However, it is still unclear how SZ risk genes interfere with NMDAR-mediated synaptic transmission in diverse inhibitory interneuron populations. One putative risk gene is neuregulin 1 (NRG1), which signals via the receptor tyrosine kinase ErbB4, itself a schizophrenia risk gene. The type I isoform of NRG1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…For instance, Li et al (2007) reported that NRG2 stimulation of ErbB4 receptors results in NMDAR internalization in PV 1 interneurons but not in pyramidal cells. Another study has shown that overexpression of NRG1 Type I, an isoform of NRG1 that has elevated levels in some SZ patients, leads to reduced NMDAR synaptic activity in hippocampal PV 1 and CCK 1 interneurons (Kotzadimitriou et al, 2018), reinforcing the idea that, regardless of which NRG-ErBb4 component is affected in SZ, its impact on interneuron's physiology may converge on NMDAR. So, the combined evidence suggests that early postnatal dysfunction of PV 1 interneurons, arising directly by altered expression of the NMDAR, or indirectly by altered function of associated pathways, may be a key triggering pathophysiological factor for the altered neurodevelopment observed in SZ.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, Li et al (2007) reported that NRG2 stimulation of ErbB4 receptors results in NMDAR internalization in PV 1 interneurons but not in pyramidal cells. Another study has shown that overexpression of NRG1 Type I, an isoform of NRG1 that has elevated levels in some SZ patients, leads to reduced NMDAR synaptic activity in hippocampal PV 1 and CCK 1 interneurons (Kotzadimitriou et al, 2018), reinforcing the idea that, regardless of which NRG-ErBb4 component is affected in SZ, its impact on interneuron's physiology may converge on NMDAR. So, the combined evidence suggests that early postnatal dysfunction of PV 1 interneurons, arising directly by altered expression of the NMDAR, or indirectly by altered function of associated pathways, may be a key triggering pathophysiological factor for the altered neurodevelopment observed in SZ.…”
Section: Discussionmentioning
confidence: 87%
“…When coupled with the observation that NMDAR antagonists cause a net disinhibition of principal cell activity (Homayoun and Moghaddam, 2007;Jackson et al, 2004), it has been suggested that cortical circuits are especially vulnerable to failure of NMDARmediated signalling in PV+ interneurons. Moreover, post-mortem studies have revealed a selective loss of PV+ interneurons in people with schizophrenia (Lewis et al, 2012) and overexpression of Neuregulin 1, a leading schizophrenia susceptibility gene, is associated with a reduction of NMDARs on PV+ cells (Kotzadimitriou et al, 2018). Destabilisation of dominant neuronal assemblies, as shown here to result from impaired NMDAR signalling on PV+ interneurons, may thus explain a failure of sensory gating (Javitt and Freedman, 2015) and evidence for reduced cognitive control, for instance in the Necker cube test (McBain et al, 2011), in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, impaired NMDAR-mediated signalling in PV+ interneurons has been suggested to be a core feature of schizophrenia (Coyle, 2012;Lisman et al, 2008). Indeed, genetic manipulation of the schizophrenia risk genes encoding neuregulin and ErbB4, which amongst other functions regulate NMDARs, impairs recruitment of PV+ interneurons and recapitulates some features of the disease (delPino et al, 2013;Kotzadimitriou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pv+ cells in mouse brain slices. Transversal slices (350 μm) from somatosensory cortex were prepared (Kotzadimitriou D et al 2018) from 4-to 6-week-old heterozygous male CB6-Tg(Gad1-EGFP)G42Zjh/J -mice (The Jackson Laboratory, stock 007677, GAD67-GFP G42 line) expressing td-Tomato fluorophore preferably in parvalbumin GABAergic neurons (Chattopadhyaya B et al 2004). Cells were confirmed to be fast-spiking, showing fast spike kinetics and a high-frequency non-accommodation firing pattern for suprathreshold depolarizing 500 ms pulses ( Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%